Pentingnya Pendidikan Multikultural Bagi Masyarakat Yang Beragam - Akhtar Safiq; Achmad Zulfikar Siregar (Jurnal Sosial Politik dan Hukum, 2024)
Indonesia consists of a variety of social diversity, ranging from race, ethnicity, religion, culture and language. However, behind this diversity, another culture was born, called the culture of anti-tolerance, and the people who belonged to this culture were generally extremist people. These radical people often destroy the unity and integrity of a nation. A strong nation is a nation that is united as one, but if there are radical seeds within it, then the nation can decline and collapse. To overcome these elements, providing multicultural education is one of the best options. Multicultural education is education that is based on the principles and principles of the concept of multiculturalism, namely the concept of diversity that recognizes, accepts and emphasizes human differences and similarities relating to gender, race, class and religion, and is based on democracy. values. Understand building cultural pluralism in business. fight prejudice and discrimination. The importance of multicultural education in Indonesia is to provide alternative ways of resolving conflicts. Multicultural education is very important for modern democracy, because students are expected not to abandon their cultural roots.